2005
DOI: 10.1161/01.hyp.0000160355.93303.72
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Failure

Abstract: Abstract-The baroreflex receives less attention nowadays because most students of hypertension are convinced that faulty volume regulation by the kidneys is responsible for long-term blood pressure increases. However, unusual patients with bilateral destruction of the normal blood pressure-sensing mechanisms can develop profound chronic hypertension. We present 2 patients with baroreflex failure. Both had volatile hypertension with systolic readings up to 300 mm Hg documented over years. Both had muscle sympat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 21 publications
0
87
0
5
Order By: Relevance
“…These data therefore provide a new line of enquiry that contributes to the debate about why goal-directed haemodynamic management in critical illness does not appear to benefit patients with established, early sepsis or systemic inflammation. 34 Defects in baroreflex function may occur in afferent neurons transmitting the information from baroreceptors, brainstem 35 Laboratory models have demonstrated that loss of vagal parasympathetic activity exacerbates systemic inflammation in several organs, through immuno-neuromodulation of α7 nicotinic receptors on tissue-resident macrophages. 36 Furthermore, vagal denervation promotes persistent inflammation through failure to regulate resolution of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These data therefore provide a new line of enquiry that contributes to the debate about why goal-directed haemodynamic management in critical illness does not appear to benefit patients with established, early sepsis or systemic inflammation. 34 Defects in baroreflex function may occur in afferent neurons transmitting the information from baroreceptors, brainstem 35 Laboratory models have demonstrated that loss of vagal parasympathetic activity exacerbates systemic inflammation in several organs, through immuno-neuromodulation of α7 nicotinic receptors on tissue-resident macrophages. 36 Furthermore, vagal denervation promotes persistent inflammation through failure to regulate resolution of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous nonphysiological electric stimulation might disturb the function of peripheral or central components of the arterial baroreflex and cause a condition resembling baroreflex failure. 32,33 This clinical state was an exclusion criterion for DEBuT-HT, and carotid sinus stimulation did not cause baroreflex deficits, as judged by different methods. If anything, in a few patients the baroreflex sensitivity increased, which could be because of true improvement in baroreflex function with an increase in the maximal slope of the sigmoidal baroreflex curve or by a shift of the operating point to the steeper portion of the curve.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 However, symptomatic orthostatic hypotension is rare unless patients become hypovolaemic, owing to reflex compensation by cardiac vagal afferents (such as low-pressure cardiac baroreceptors) that remain intact. [28][29][30] Patients with familial dysautonomia (Riley-Day syndrome or hereditary sensory neuropathy type III) Note that aortic baroreceptors, which also influence blood pressure, are not paced. The dashed arrows represent inhibitory neural influences, and solid arrows represent excitatory neural influences on sympathetic outflow to the heart, peripheral vasculature, and kidneys.…”
Section: Efferent Armmentioning
confidence: 99%